Tipping point: The staff wellbeing crisis in higher education - Jayman, Michelle; Glazzard, Jonathan; Rose, Anthea (Frontiers in Education, 2022)
This marketised higher education environment in the UK has had dire consequences for academics at all levels. Literature suggests that academics are busier and working faster than ever. There is evidence of an undermining of academic professionalism, academic freedom and increased job insecurity in the sector. It is not possible for academics to position themselves outside of the performance culture and still be viewed as a valued team member. Within this paper, our concerns relate specifically to the impact of this culture of performativity on the wellbeing of staff who work in UK higher education institutions.